2012
DOI: 10.1016/j.juro.2012.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cryptorchidism Diagnoses and Corrective Surgical Treatment Registration in the Danish National Patient Registry

Abstract: The data on cryptorchidism in the Danish National Patient Registry are quite accurate. In etiological research the limited misclassification will in most cases only slightly attenuate estimates of the true relative association. Thus, the registry has the potential to serve as a valuable research tool, although caution should be exercised when studying time trends or geographical differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…Therefore hypospadias reported in the Danish National Patient Registry presumably to a larger degree include more severe than mild cases. Nevertheless, the observed prevalences of 2.5% and 0.4% of cryptorchidism and hypospadias, respectively, in the cohort of sons of employed mothers resemble those reported in other studies (9)(10)(11)(12)(13)(14), and high positive predictive values have been found for the diagnosis of cryptorchidism (80%) and the registration of orchiopexy (99%) in the Danish National Patient Registry (37). Finally, the Danish healthcare system is free of charge and accessible to all Danish citizens, and we do not expect underestimation of cryptorchidism and hypospadias to differ between the occupational groups examined in this study.…”
Section: Jørgensen Et Alsupporting
confidence: 87%
“…Therefore hypospadias reported in the Danish National Patient Registry presumably to a larger degree include more severe than mild cases. Nevertheless, the observed prevalences of 2.5% and 0.4% of cryptorchidism and hypospadias, respectively, in the cohort of sons of employed mothers resemble those reported in other studies (9)(10)(11)(12)(13)(14), and high positive predictive values have been found for the diagnosis of cryptorchidism (80%) and the registration of orchiopexy (99%) in the Danish National Patient Registry (37). Finally, the Danish healthcare system is free of charge and accessible to all Danish citizens, and we do not expect underestimation of cryptorchidism and hypospadias to differ between the occupational groups examined in this study.…”
Section: Jørgensen Et Alsupporting
confidence: 87%
“…also, the study has a long follow-up time of up to 30 years, thus allowing complete ascertainment of cryptorchidism cases. 37 the diagnostic entries of cryptorchidism in the national Patient registry have been validated based on 500 randomly chosen cases, with an overall positive predictive value of 80% (95% ci = 77-84%), which increased to 99% (98-100%) when the diagnosis was confirmed by surgical treatment of the condition. 37…”
Section: Strengthsmentioning
confidence: 99%
“…Furthermore, the validation study covered only the icD-10 era, leaving the positive predictive values of the icD-8 codes undocumented. 37 also, the cryptorchidism diagnoses from the register include boys with undescended testis at birth that later descend spontaneously. 37 Some additional misclassification may arise due to differences in the hospital doctors' examination technique.…”
Section: Strengthsmentioning
confidence: 99%
See 2 more Smart Citations